If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9 = 6r + -13 Reorder the terms: -9 + 4x = 6r + -13 Reorder the terms: -9 + 4x = -13 + 6r Solving -9 + 4x = -13 + 6r Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4x = -13 + 9 + 6r Combine like terms: -9 + 9 = 0 0 + 4x = -13 + 9 + 6r 4x = -13 + 9 + 6r Combine like terms: -13 + 9 = -4 4x = -4 + 6r Divide each side by '4'. x = -1 + 1.5r Simplifying x = -1 + 1.5r
| 7x=5x-18 | | 9mn+p=2k | | 10/2+1=6 | | -8(x+9)=-96 | | b^2+6b-x^2+9=0 | | 5=4x+4 | | p/2+1=6 | | -91=-7(x+2) | | 6x+20=34 | | -2y-7=-13 | | 7b+12=31b | | 4(-0.4+-0.29)-3y=-13 | | 8x+22=-28 | | -6x+(7x+2)-(x-9)=19 | | |3x-8|-|3x-2|=6 | | 44-3x=8-9x | | 9x+1=8x+2 | | 11+(2-9x)=15-(2x+9) | | -11=6b+5b | | 5x-20=x+3 | | y^3=8-x | | 5z-2(z-8)=3(y-3z)+12 | | -9c-(-7c+1)=16 | | 24n=15n-81 | | 5+7+2+6+y+(y+1)+7+4=5 | | (x+7)(7x-1)=x+3 | | (3x-11)+(2x+7)= | | -3a-(a+2)-(a-4)=5a | | -4x+33= | | (3x-5)(x+14)=0 | | 7+30x=20x+15 | | 5+4X=-8 |